Politicians' Motivation, Political Culture, and Electoral Competition - Klaas J. Beniers; Robert Dur (Tinbergen Institute, 2004)
We study electoral competition among politicians who are heterogeneous both in competence and in how much they care about (what they perceive as) the public interest relative to the private rents from being in office. We show that politicians may have stronger incentives to behave opportunistically if other politicians are more likely to behave opportunistically. A political culture may therefore be self-reinforcing and multiple equilibria may arise. We also show that politicians' incentives to behave opportunistically increase with politicians' pay and with polarization of policy preferences.
Keywords: D72; D78; 330; politicians' motivation; politicians' pay; political culture; electoral competition; coalition governments; reputation bashing; Politiker; Motivation; Neue politische Ökonomie; Theorie; Politische Kultur; Wahlkampf